Hydration of the phosphate group in double-helical DNA - Schneider, B; Patel, K; Berman, H M (Biophysical journal, 1998)
Water distributions around phosphate groups in 59 B-, A-, and Z-DNA crystal structures were analyzed. It is shown that the waters are concentrated in six hydration sites per phosphate and that the positions and occupancies of these sites are dependent on the conformation and type of nucleotide. The patterns of hydration that are characteristic of the backbone of the three DNA helical types can be attributed in part to the interactions of these hydration sites.
Keywords: molekulární modely; voda; DNA; Models, Molecular; oligodeoxyribonukleotidy; Binding Sites; konformace nukleové kyseliny; Nucleic Acid Conformation; vazebná místa; Oligodeoxyribonucleotides; Phosphates; Water; fosfáty